Teachers’ Knowledge, Attitudes, and Practices Towards Inclusion for Students with Emotional and Behavioural Disorders in Dubai’s Private Mainstream Schools - AYOUB, LAMA SAIF ALDEE (2025)
This research explores the attitudes, knowledge, and practices of educators in Dubai’s private mainstream schools related to the inclusion of students with Emotional and Behavioural Disorders (EBDs). The mixed-methods approach is utilised and the data were collected through a survey and semi-structured interviews with educators. The sample size was 37 for the survey while it was 10 for the interviews. The results revealed different levels of familiarity with the EBD traits, the inconsistent implementation of inclusive practices, and the general requirement for targeted professional development. Most of the educators showed positive attitudes towards inclusion. However, major gaps in training and institutional support were noted. Structural challenges like limited behavioural support staff along with big class sizes also hampered effective implementation. The research indicates the significance of ongoing training along with policy alignment and collaborative support systems to enhance inclusive education for students with EBDs. This study contributes to the limited body of knowledge in the UAE context and provides practical suggestions for inclusive education practice and policy.